The Effect of Co-branding Strategy on Impulse Purchase Intention and Attitudes towards Parent Brands in Chinese Sneaker Industry - Wu, Zhennan (2020)
Co-branding strategy has been an attractive approach for business and brands to expand their business and to obtain more customer awareness. Within the fashion industry, sneaker brands are also building alliances with other types of brands frequently. Due to the low availability of certain co-branded sneakers, consumers with the need for uniqueness are the main buyers and their familiarity with the parent brands appears to affect their impulse purchase behaviours and attitudes towards parent brands. This research examines the effect of co-branding strategy on the impulse purchase intention and attitudes to parent brands in terms of parent brand familiarity and need for uniqueness, taking Chinese sneaker industry for example. The study includes six sneaker collaboration examples in three co-branding categories and uses a valid sample of 319 Chinese participants and the linear regression model as the analysis tool. The research confirms how the independent variables (parent brand familiarity and need for uniqueness) positively affect dependent variables (impulse purchase intention and attitudes towards parent brands). These findings provide insights on how the co-branding strategy in the sneaker industry strengthen the impulse purchase intention and enhance consumers’ attitudes. Comparisons on three collaboration categories also provide brands with suggestions on achieving goals on either stimulating impulse purchase or strengthen consumers attitudes.